2001
DOI: 10.1265/ehpm.2001.149
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Cardiac Autonomic Nerve Activity in Healthy Children: Results of the Toyama Birth Cohort Study

Abstract: Objectives: To determine the relationship between obesity and cardiac autonomic nerve activity in healthy children. Methods: 16 healthy male children comprising of 9 nonobese and 7 obese subjects (body mass index > 19.1 kg/m 2) aged 8 9 years were selected. Electrocardiograms were measured for 10 min. under controlled ventilation (0.25 Hz) in the supine position. Consecutive 256-second RR interval data were transformed by the Fast Fourier Transform method into power spectral data. Very low frequency (VLF; 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…The reduction in heart rate variability evident in overweight/obese children supports findings by Karason et al (1999) and Sekine et al (2001) who reported a reduction in parasympathetic activity and withdrawal of vagal modulation, which is reflected by decreased RMSSD with increasing BMI. These findings may indicate reduced receptor responsiveness and/or increased sympathetic efferent outflow (Tentolouris et al, 2006) in children with higher BMI values.…”
Section: Discussionsupporting
confidence: 85%
“…The reduction in heart rate variability evident in overweight/obese children supports findings by Karason et al (1999) and Sekine et al (2001) who reported a reduction in parasympathetic activity and withdrawal of vagal modulation, which is reflected by decreased RMSSD with increasing BMI. These findings may indicate reduced receptor responsiveness and/or increased sympathetic efferent outflow (Tentolouris et al, 2006) in children with higher BMI values.…”
Section: Discussionsupporting
confidence: 85%
“…The literature shows conflicting data regarding the indices of HRV in obese children (Sekine et al, 2001;Yakinci et al, 2000;Nagai et al, 2003;Nagai and Moritani, 2004;Kaufman et al, 2007). According to Nagai et al (2003) these differences may be related to the difficulty of controlling the variables including: age, gender, history of obesity, medical complications, dietary and behavioral habits, physical activity and emotional stress.…”
Section: Variables Girls Boysmentioning
confidence: 99%
“…Studies involving obesity in children and the analysis of the ANS through the assessment of HRV have presented conflicting results. Analyzing HRV indices in the frequency domain, Sekine et al (2001) suggest that obese children exhibit higher sympathetic activity and lower parasympathetic activity in comparison to children within the normal weight range. However, Nagai et al (2003) and Nagai and Moritani (2004) found both sympathetic and parasympathetic activities to be reduced in obese children.…”
Section: Introductionmentioning
confidence: 99%
“…The linear indexes in the frequency domain, very low‐frequency spectral component varying from 0.003 to 0.04 Hz (VLF), low‐frequency spectral component varying from 0.04 to 0.15 Hz (LF), high‐frequency spectral component varying from 0.15 to 0.4 Hz (HF); expressed in ms 2 or normalized units, and the spectral component varying from 0.003 to 0.4 Hz (Total Power) 21,22 were calculated through the fast Fourier transform.…”
Section: Methodsmentioning
confidence: 99%